Arthroscopic simulation in skills training: European initiatives - (:unkn) unknown (Springer Berlin Heidelberg, 2014)
Arthroscopic surgery has become the leading operative therapy for a growing number of injuries. Obtaining arthroscopic skills is quite challenging, due to reduced visibility and dexterity of instruments, disturbed eye-hand coordination and loss of force and tactile feedback. That is why learning arthroscopic skills takes considerable time and implicates an increased risk of surgical errors during the early stages of the learning curve when operating on patients. As patient safety and competence in surgery are of utmost importance to fulfil requirements of high-quality healthcare, there is a need for efficient and effective training. © ESSKA 2014.